A study on sector index of stock market proposal for development of FPTS sector index : Luận văn ThS. Kinh doanh và quản lý: 60 34 05 - Nguyễn, Minh Khôi (Đại học Quốc gia Hà Nội, 2017)
69 p. + CD-ROM